FAST FASHION DAN KEBERLANJUTAN BISNIS: INTERVENSI STRATEGIS UNTUK INDUSTRI MELALUI CAUSAL LOOP DIAGRAM ANALYSIS - Sari, Dewi Purnama; Pambudi, Ivan Agus Setiawan (ANALISIS, 2025)
The fast fashion industry has rapidly grown into a dominant business model in the global apparel sector, driven by consumer demand for affordable and trend-oriented clothing. However, the widespread adoption of this model has raised significant environmental, social, and economic concerns. This article aims to analyze the fast fashion industry phenomenon as a systemic issue using secondary data and a systems thinking approach through a causal loop diagram. The findings reveal the industry’s substantial contribution to climate change, water pollution, microplastic waste, and labor exploitation. Key actors include the government, the fast fashion textile industry, consumers, models, influencers, workers, and investors, each with distinct mental models. By identifying leverage points, the study concludes that digital technology–based intervention strategies can be implemented to support behavioral transformation among consumers and business actors, including MSMEs in the sustainable fashion sector.